Mobilising trade policy for climate action under the Paris agreement: Options for the European Union - Susanne Dröge; Harro van Asselt; Kasturi Das; Michael Mehling (Stiftung Wissenschaft und Politik (SWP), 2018)
The European Union (EU) has been advocating climate policy ambitions from the very beginning of the international climate regime. Climate action to support the implementation of the Paris Agreement (2015) involves nearly all fields of national and international policy-making. In this research paper, we look into the role of trade policy in this respect. There are several legal and institutional options for how policy-makers in the EU and elsewhere could promote a productive relationship between the UN climate regime and the international trade regime, comprising the World Trade Organization (WTO) and regional trade agreements (RTAs). The increasing number of WTO disputes over national renewable energy policy regulations points to a systemic conflict between national climate policies and WTO obligations, whereas a number of RTAs including environmental standards demonstrate positive ways forward, in particular on how to avoid a race to the bottom. As a longer-term vision, we identify the legal options under the WTO regime, and for the medium term we suggest synergies that the EU can achieve through RTA negotiations and reviews. In the short term, the EU and its Member States should push for more transparency on trade-related climate measures, for example through notifications, between the bodies of the WTO and the United Nations Framework Convention on Climate Change, as well as follow up with climate policy allies on trade initiatives that support the climate agenda.
Keywords: 320; Conference of the Parties to the UN Framework Convention on Climate Change 21. (Paris; 2015-11-30/2015-12-11); Kohlendioxid; Emissionsreduktion; Internationale Verpflichtungen